A new approach for signal and noise FET modeling including wave propagation effects. (6th August 2015) - Asadi, Shahrooz; Yaghoub, Mustapha C. E.; Biabanifard, Sadegh; Caddemi, Alina; Caddemi, Ernesto
Abstract In the millimeter‐wave frequency range, electromagnetic effects can significantly influence a device behavior. As the core of modern communication systems, active devices such as field‐effect transistors require up‐to‐date models to accurately integrate such effects, especially in terms of noise performance because most of communication systems operate in noisy environments. Based on the active coupled line concept, a novel approach for efficient noise performance modeling of millimeter‐wave field‐effect transistors is proposed. This distributed model considers the effect of wave propagation along the device electrodes, which can significantly affect the noise performance, especially in the millimeter‐wave range. Copyright © 2015 John Wiley & Sons, Ltd.